Local and Global Dynamics in a Discrete Time Growth Model with Nonconcave Production Function - Serena Brianzoni; Cristiana Mammana; Elisabetta Michetti (Discrete Dynamics in Nature and Society)
We study the dynamics shown by the discrete time neoclassical one-sector growth model with differential savings while assuming a nonconcave production function. We prove that complex features exhibited are related both to the structure of the coexixting attractors and to their basins. We also show that complexity emerges if the elasticity of substitution between production factors is low enough and shareholders save more than workers, confirming the results obtained while considering concave production functions.